2020
DOI: 10.1088/1742-6596/1430/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of fasciolosis emphasis on age, origin, body condition and post mortem by geographic information systems on sacrificial examination in Malang District – East Java

Abstract: Infection with Fasciola gigantica, a liver trematode, is frequently reported in Malang district. The study was aimed to determine the prevalence of fascioliasis in Malang District, East Java during Eid Qurban 2019. Data were collected from 68 cutting points in 9 sub-districts. A total of 265 cows, 895 goats and 112 sheep than analyzed based on questioner emphasis on age, origin, body condition, and postmortem abnormalities. Overall the highest prevalence of fasciolosis was 57% cattle and 18% goat in Gondangleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
2
7
0
1
Order By: Relevance
“…Despite the livestock system used in the two study areas, the farmers of the Imbo region who live and raise their livestock near the lake, rivers, and the marshes where they grow rice, have a habit of drawing water for watering livestock in these areas without being treated. The later result is also in the same line to the prevalence of 30.9% reported by Elshraway and Mahmoud ( 2017 ) in an abattoir of El-Kharga of Egypt, 30% reported by Kusumarini et al ( 2020 ) in Malang District, East Java in Indonesia, and 39.1% reported by Tulu and Gojam ( 2018 ) in Western of Ethiopia using the same method in abattoir. Other studies in the same line with the current study were reported by Mequaninit ( 2021 ) with the prevalence of 35% in Kombolcha ELFORA abattoir located in the North Eastern part of Ethiopia, reported by Bernardo et al ( 2011 ) with the prevalence of 24.9% in the Southern Espirito Santo and reported by Mungube et al ( 2006 ) with the prevalence of 26% in semi-arid coastal part of Kenya.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Despite the livestock system used in the two study areas, the farmers of the Imbo region who live and raise their livestock near the lake, rivers, and the marshes where they grow rice, have a habit of drawing water for watering livestock in these areas without being treated. The later result is also in the same line to the prevalence of 30.9% reported by Elshraway and Mahmoud ( 2017 ) in an abattoir of El-Kharga of Egypt, 30% reported by Kusumarini et al ( 2020 ) in Malang District, East Java in Indonesia, and 39.1% reported by Tulu and Gojam ( 2018 ) in Western of Ethiopia using the same method in abattoir. Other studies in the same line with the current study were reported by Mequaninit ( 2021 ) with the prevalence of 35% in Kombolcha ELFORA abattoir located in the North Eastern part of Ethiopia, reported by Bernardo et al ( 2011 ) with the prevalence of 24.9% in the Southern Espirito Santo and reported by Mungube et al ( 2006 ) with the prevalence of 26% in semi-arid coastal part of Kenya.…”
Section: Discussionsupporting
confidence: 84%
“…A total of 467 cattle were randomly selected during ante-mortem and individual information including date, cattle owner, origin, sex, age, breed, body condition score and clinical signs were recorded in notebooks. During post-mortem inspection, the liver and associated bile ducts and gallbladders were carefully examined for the presence or absence of liver fluke using visualization, palpation and incision with a knife (Kusumarini et al 2020 ). Liver lesions were then grouped based on the liver fluke burden into mild infection (1–29 flukes), moderate infection (30–50 flukes) and heavy infection (> 50 flukes) (Mpisana et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…There was no statistically significant association observed on the prevalence among animals of different sex in this study. This result is similar with the results of several other studies (Kusumarini et al, 2020) who also reported statistically insignificant association between prevalence and sex and concluded that Fasciola infections have no sex predisposition. The findings by Nagwa and Wafaa (2017) reported that bulls are usually brought to the Abattoir for slaughter than cows which is in the tradition of cattle producers in many locations.…”
Section: Comparison Of Diagnostic Agreement Between Flukefinder® Kit ...supporting
confidence: 92%
“…The Indonesian government regularly conducts extension programs to enhance farmers' knowledge of livestock management, feed, reproduction, and animal health. Information regarding fasciolosis is an important part of the program since the disease is commonly reported in animals sacrificed during Eid al-Adha [30,78]. Extension programs may become a useful instrument for disseminating information to rural communities, and it is a powerful medium for increasing farm productivity [79,80].…”
Section: Discussionmentioning
confidence: 99%